Reducing Postoperative Opioids for Outpatient Endoscopic Urological Surgery: A Resident Driven Quality Improvement Initiative. Issue 5 (14th September 2020) - Narayan, Vikram M.; Lane, Giulia; Sukumar, Shyam; Nakib, Nissrine; Ordonez, Maria A.
Abstract: Introduction: Opioid dependency has become a public health crisis in the United States and surplus prescriptions of opioids after surgery may be contributing to this problem. This resident driven quality improvement initiative sought to study the prescribing patterns of opioids for patients undergoing outpatient urological surgery at our institution, reduce prescriptions where possible and monitor patient outcomes. Methods: A chart review and telephone survey were conducted of patients undergoing outpatient endourological surgery. Type and quantity of narcotics prescribed were identified, and patients were surveyed on quantity of medication consumed. Physicians were then counseled on prescribing quantities closer to the average amounts reportedly used by patients. After 30 days we assessed emergency room visits, readmissions and telephone calls related to pain. Results: Before our initiative patients were prescribed an average of 156.6 morphine milligram equivalents (median 150) after endourological surgery. Patients reported using between 0–37.5 morphine milligram equivalents, with 71% reporting using no narcotics. Following 30 days of surgeon advisement, the average prescription decreased to 38.6 morphine milligram equivalents (median 0), representing a 75.3% reduction. Following reductions there were no significant differences in emergency room visits, telephone calls, readmissions or rate of drug refills. Conclusions: Resident driven quality improvement initiatives can lead to reductions in the prescription of surplus opioids after certain types of urological surgery. These efforts can play an important role in reducing the supply of available narcotics at the local level.